Optimizing geometry of extruded PMMA microstructured optical fiber preforms - Sia, Johnathan Seng Hong (2017)
Photonic crystal fibers are now widely research on its applications due to the special properties. One of such application is sensor. By designing the photonic crystal fiber with different geometry, it can adjust the sensitivity as a strain or temperature sensor. Sensitivity is important when comes into play as a sensor as a minute change in parameter will have adverse effect on certain research.